A Novel Protective MHC-I Haplotype Not Associated with Dominant Gag-Specific CD8(+) T-Cell Responses in SIVmac239 Infection of Burmese Rhesus Macaques - Takahashi, Naofumi (Public Library of Science, 2013)
Several major histocompatibility complex class I (MHC-I) alleles are associated with lower viral loads and slower disease progression in human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) infections. Immune-correlates analyses in these MHC-I-related HIV/SIV controllers would lead to elucidation of the mechanism for viral control. Viral control associated with some protective MHC-I alleles is attributed to CD8(+) T-cell responses targeting Gag epitopes. We have been trying to know the mechanism of SIV control in multiple groups of Burmese rhesus macaques sharing MHC-I genotypes at the haplotype level. Here, we found a protective MHC-I haplotype, 90-010-Id (D), which is not associated with dominant Gag-specific CD8(+) T-cell responses. Viral loads in five D(+) animals became significantly lower than those in our previous cohorts after 6 months. Most D(+) animals showed predominant Nef-specific but not Gag-specific CD8(+) T-cell responses after SIV challenge. Further analyses suggested two Nef-epitope-specific CD8(+) T-cell responses exerting strong suppressive pressure on SIV replication. Another set of five D(+) animals that received a prophylactic vaccine using a Gag-expressing Sendai virus vector showed significantly reduced viral loads compared to unvaccinated D(+) animals at 3 months, suggesting rapid SIV control by Gag-specific CD8(+) T-cell responses in addition to Nef-specific ones. These results present a pattern of SIV control with involvement of non-Gag antigen-specific CD8(+) T-cell responses.